Educators perceptions of family risk factors associated with child sexual abuse: the case of Gweru primary schools - Shoko, N. (Midlands State University, 2015)
The study sought to establish educators perceptions of family risk factors associated with child sexual abuse among children in Gweru urban primary schools. A descriptive survey was adopted to carry out the study. A total of thirty educators, comprising of five school heads and twenty five teachers, all purposively selected, participated in the study. The teachers responded to a questionnaire while face to face interviews were carried out with the school .heads. The study established that educators perceived changes in the family structure, poverty in the family, parenting styles and parental personality factors as the major factors associated with child sexual abuse. The study concluded that the family was central to child safety. The major recommendations for the study were that there was need to carry out vigorous awareness campaigns on child safety within the communities. The study also recommended that school authorities should be encouraged to investigate and report to the Social Services Department all cases of children living in child headed families so that the department takes measures to ensure that such children get community protection and support.